2013
DOI: 10.1038/nsmb.2707
|View full text |Cite
|
Sign up to set email alerts
|

Cks confers specificity to phosphorylation-dependent CDK signaling pathways

Abstract: Cks is an evolutionarily conserved protein that regulates cyclin-dependent kinase (Cdk) activity. Clarifying the underlying mechanisms and cellular contexts of Cks function is critical, as Cks is essential for proper cell growth, and its overexpression has been linked to cancer. We observe that budding yeast Cks associates with select phosphorylated sequences in cell cycle regulatory proteins. We characterize the molecular interactions responsible for this specificity and demonstrate that Cks enhances Cdk acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 52 publications
(86 reference statements)
7
126
0
Order By: Relevance
“…For example, the response of Cdc25C to Cdk1 is more highly ultrasensitive than one would obtain from a non-cooperative multisite phosphorylation mechanism (Fig 1C). Moreover, Cdc25C possesses phosphorylation sites that conform well to the Cks binding consensus (T48, T67, and T138), and elimination of these sites changes the response of Cdc25C from ultrasensitive to Michaelian (Fig 1C) [9, 12]. These results suggest that priming generates cooperativity and cooperativity contributes to the highly ultrasensitive response seen in this system.…”
Section: Priming and Cooperativity In Multisite Phosphorylationmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, the response of Cdc25C to Cdk1 is more highly ultrasensitive than one would obtain from a non-cooperative multisite phosphorylation mechanism (Fig 1C). Moreover, Cdc25C possesses phosphorylation sites that conform well to the Cks binding consensus (T48, T67, and T138), and elimination of these sites changes the response of Cdc25C from ultrasensitive to Michaelian (Fig 1C) [9, 12]. These results suggest that priming generates cooperativity and cooperativity contributes to the highly ultrasensitive response seen in this system.…”
Section: Priming and Cooperativity In Multisite Phosphorylationmentioning
confidence: 83%
“…The phosphorylation of the first Thr (T) site primes the substrate for phosphorylation of the second Ser (S) residue as a result of the interaction of the pThr epitope with the Cks subunit, and can make the second phosphorylation be more favorable than the first. Adapted from [12]. …”
Section: Figmentioning
confidence: 99%
“…These results imply that Far1 inhibits substrate docking strongly, with a residual effect on some non-docking function such as Cdk kinase activity. This residual effect might also signify a reduction in kinase processivity mediated by the Cks1 subunit of the Cdk complex [1820], though it was still evident when the role of Cks1 was blocked (by changing threonine phosphorylation sites to serine; Figure S4D). It is also notable that this residual effect was only seen with the G1/S cyclins Cln1 and Cln2 (Figure 4D), even though Far1-S87A could bind all cyclins (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…This mutant also revealed that inhibitory effects of Far1 are at least partly independent of T306 phosphorylation. Yet, T306 phosphorylation makes Far1 a more potent inhibitor, likely via enhanced binding to Cdk complexes [5] and possibly via engaging the phospho-threonine binding pocket in Cks1 [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the docking function of Cln2 was required for multi-site phosphorylation of substrates, which involves processive catalysis and the Cks1 subunit of the cyclin-CDK-Cks1 complex [15, 42]. Thus, in vivo, events that require extensive substrate phosphorylation may be especially dependent on docking, and this could underlie some functional distinctions among G1 cyclins.…”
Section: Discussionmentioning
confidence: 99%